Experimental Performance Analysis of an Electromagnetic Energy Harvester Driven by Flow-Induced Vibration - Subekti, Subekti; Paduloh, Paduloh; Saidiman, Mochamad (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: This study aims to experimentally investigate the performance of an electromagnetic energy harvester driven by flow-induced vibration (FIV) under airflow conditions representative of building ventilation systems. A cylindrical oscillator integrated with a magnet–coil transduction mechanism was tested in a wind tunnel at airflow velocities of 0.5 m/s, 2 m/s, and 4 m/s. Vibration responses were measured using an FFT analyzer, while the electrical output was recorded using a digital oscilloscope and processed to obtain RMS voltage and average power. The results show that the harvested power at 2 m/s is approximately four times that obtained at 0.5 m/s, indicating optimal performance within the lock-in region, where the vortex-shedding frequency approaches the structure's natural frequency. Although higher airflow velocity increases the vibration amplitude, the average harvested power at 4 m/s decreases due to partial detuning and increased damping. These findings demonstrate that moderate airflow velocities provide optimal operating conditions for electromagnetic energy harvesting and highlight the feasibility of integrating airflow-based vibration energy harvesters into building systems to power low-energy devices. Abstrak: Penelitian ini bertujuan untuk mengkaji secara eksperimental kinerja pemanen energi elektromagnetik yang digerakkan oleh getaran akibat aliran fluida (flow-induced vibration) pada kondisi aliran udara yang merepresentasikan sistem ventilasi bangunan. Sebuah silinder elastis yang terintegrasi dengan mekanisme transduksi magnet–kumparan diuji di dalam terowongan angin pada kecepatan aliran 0,5 m/s, 2 m/s, dan 4 m/s. Respons getaran diukur menggunakan FFT analyzer, sedangkan keluaran listrik direkam menggunakan osiloskop digital dan dianalisis untuk memperoleh tegangan RMS serta daya rata-rata. Hasil penelitian menunjukkan bahwa daya yang dihasilkan pada kecepatan 2 m/s sekitar empat kali lebih besar dibandingkan dengan 0,5 m/s, yang menunjukkan kondisi operasi optimal pada daerah lock-in ketika frekuensi pelepasan pusaran mendekati frekuensi alami struktur. Meskipun peningkatan kecepatan aliran memperbesar amplitudo getaran, daya rata-rata pada 4 m/s menurun akibat efek detuning parsial dan peningkatan redaman sistem. Temuan ini menunjukkan bahwa kecepatan aliran sedang merupakan kondisi optimal untuk pemanenan energi elektromagnetik serta menegaskan potensi integrasi sistem ini pada infrastruktur bangunan untuk menyuplai perangkat berdaya rendah.